Dose and application rate of fungicide to control leaf rust (Puccinia triticina) and yellow spot (Pyrenophora tritici repentis) of wheat - Gustavo Migliorini de Oliveira; Diego Dionizio Pereira; Lênio César Moraes de Camargo; Marcelo Gonçalves Balan; Marcelo Giovanetti Canteri; Seiji Igarashi; Otavio Jorge Grigoli Abi Saab (Semina: Ciências Agrárias, 2015)
The aim of this paper was to study the role of dose and rate of application, and the effect of concentration of fungicide in the spray solution resulted from the interaction of these factors, in the control of leaf rust and yellow spot of wheat. It was conducted two experiments, the first used the CD 104 cultivar (susceptible to lead rust and yellow spot). The experimental design was an factorial 3 x 3 + untreated control, that involve the factors dose (0,25, 0,30 and 0,35 L.ha-1) and application rate (143, 286 and 429 L.ha-1). The second experiment used the BRS 208 cultivar (resistant to leaf rust and moderately resistant to yellow spot). The experimental design was an factorial 2 x 2 + untreated control, consisting the factors dose (0,2 and 0,3 L.ha-1) and application rate (143 and 286 L.ha-1). The applications were made with a coastal sprayer by CO2, pressure of 250 kPa, XR 110-02 nozzle, which generated an application rate of 143 L.ha-1. The respective rates of each treatment were changed by the number of sprayers per area. It was also used a spore trap denominated Siga, associated with meteorological data and weather forecast, which detected spores of rust and yellow spot before the symptoms in the plants, helping in the identification of disease and in the timing of application. There wasn´t any interaction between dose and rate of application for any of the experiments, therefore, there wasn´t effect of concentration of fungicide in control. The dose and rate of application just influenced in the control of the yellow spot. Higher doses and rates were more effective. However, no difference was observed for yield and hectolitre weight among treatments, except untreated control